Mandate daze: stories of British rule in Palestine, 1917-48 - Bunton, Martin (International journal of Middle East studies, 2003)
Enthält Rezensionen u.a. von: Segev, Tom: One Palestine, complete: Jews and Arabs under the British mandate. - New York: Metropolitan Books, 2000